Membrane-anchored calpains – hidden regulators of growth and development beyond plants? - Martin Šafranek; Alain Shumbusho; Wenche Johansen; Júlia Šarkanová; Stanislav Voško; Boris Bokor; Boris Bokor; Ján Jásik; Viktor Demko; Viktor Demko (Frontiers in Plant Science, 2023)
Calpains are modulatory proteases that modify diverse cellular substrates and play essential roles in eukaryots. The best studied are animal cytosolic calpains. Here, we focus on enigmatic membrane-anchored calpains, their structural and functional features as well as phylogenetic distribution. Based on domain composition, we identified four types of membrane-anchored calpains. Type 1 and 2 show broad phylogenetic distribution among unicellular protists and streptophytes suggesting their ancient evolutionary origin. Type 3 and 4 diversified early and are present in brown algae and oomycetes. The plant DEK1 protein is the only representative of membrane-anchored calpains that has been functionally studied. Here, we present up to date knowledge about its structural features, putative regulation, posttranslational modifications, and biological role. Finally, we discuss potential model organisms and available tools for functional studies of membrane-anchored calpains with yet unknown biological role. Mechanistic understanding of membrane-anchored calpains may provide important insights into fundamental principles of cell polarization, cell fate control, and morphogenesis beyond plants.